With Dissolution Comes Revelation: Civil Partners Discover the Economic Basis of Marriage - Auchmuty, Rosemary (feminists@law, 2013)
It has been argued that one of the reasons for the decline in the rate of heterosexual marriage in western coutnries has been women's increased economic power, with the availability of alternative means of support making marriage to a breadwinning husband less essential and, in fact, less likely. Indeed, the reciprocity of marital support obligations on divorce has made it financially disadvantageous for women at both ends of the wealth spectrum to formalise relationships with dependent men. The absence of a gendered power dynamic in same-sex relationships has led some advocates of same-sex marriage to present the institution as a new, equality-based model for all marriages. Such a representation ignores the profound, historical and continuing economic basis of marriage and the fact that protection of an economically weaker partner lies at the heart of our marriage laws. The Civil Partnership Act 2004 was welcomed for conferring (near) equality on same-sex relationships, but what legal recognition actually meant in terms of obligations was often lost sight of in the rush to get 'married'. As with heterosexual marriage, however, it is only on the ending of a relationship that the true effects of legal regulation become clear. Interviews conducted with people who have dissolved their civil partnership reveal that, for those with property to dispute over, the court's discretion on dissolution to override previously agreed arrangements or understandings often comes as an expensive surprise. This paper explores the effects that ignorance or greater undersanding of the economic effecs of legal regulation might have on decisions made by same-sex couples.